CYBER TERRORISM: A POTENTIAL THREAT TO GLOBAL SECURITY - Sebastian, Jobin; Sakthivel, P. (PEARSON JOURNAL, 2020)
A large portion of the average folks across the world is unconscious about the menace of cyber terrorism. Today cyber terrorism has emerged as a potential threat to the very existence of sovereign states and thrown challenges to national as well as international security. Most of the developed and developing nations are well-outfitted measures to tackle any challenges from conventional terrorism. In the era of technocracy, ICT enabled devices such as computers, mobile phones, social media, etc. have become perfect tools to wage neo or cyberwarfare with democratically elected governments all around the world. Even in the amidst COVID–19 pandemic situation, Data theft, breaching of privacy of individuals, unauthorized access to COVID–19 related health research, virus attacks, ransomware attacks etc. are penetrating every day. By cyber terrorism, the terrorist can crush the whole digital administration and financial arrangement of a nation. Now it has become a compulsion that, most of the countries especially developed and developing countries are investing more money for strengthening their cybersecurity system. The wide use of cyberspace for communication, administration, business etc. and lack of cybersecurity awareness made the alarming growth of cyber terrorism. Besides, the lack of uniform and strong international rules and regulations and lack of modification of existing rules dangerously help cyber terrorism. This paper attempts to comprehend the development of cyber terrorism and how it has posed challenges or potential threat to global security.